Confessional factor in migrants’ adaptation proces - Svetlana Mikova, Viktor Shaklein (Opción, 2019)
The main objective of the paper is a research of the confessional factor as an important component of the solution of the problem of social adaptation of Muslims in the Russian society. Along with the methods of historico-comparative, statistical analysis of the data was used. As a result, the discussion on Muslims living in Europe has two directions: the multiculturalism theory and the concept of constant integration of Muslims into the European society. In conclusion, the authors emphasize on the existing programmes aimed at the regulation of the social adaptation of Muslim migrants in Russia